Wrath - Davies, Anne (Docklands, Vic. JoJo Publishing, 2014)
Luca has been sent to juvenile dentention for killing his mother and stepfather but refuses to tell why he committed the crime. There he lives in a world of darkness and violence. But will Luca finally find something that allows him to tell his side of the story? Based on a real-life story where a 24-year-old Tennessee man was executed for murdering his mother and step-father when he was 13. He had been on drugs and had access to a gun.
"After committing an horrific crime can Luca finally achieve redemption"--Cover.
For juveniles.
Recipient of the Children's Book Council of Australia "Book of the Year Awards Notables 2015" (Older Readers)
Keywords: Prisoners -- Juvenile fiction; Murderers -- Juvenile fiction; Teenagers -- Juvenile fiction; Prisoners -- Juvenile fiction; Juvenile detention -- Juvenile fiction; Young adult fiction; Western Australia -- Juvenile fiction; Australian; Young adult fiction